Auditor Liability and Client Acceptance Decisions - Laux, Volker; Paul Newman, D. (The Accounting Review, 2010)
ABSTRACT: The accounting profession has raised concerns that excessive liability exposure renders audit firms unwilling to provide audit services to risky clients, limiting the prospective clients' ability to raise external capital. We address this concern in a model in which the auditor evaluates the riskiness of the client before accepting the client engagement. We consider a setting in which a shift to stricter legal liability regimes not only increases the expected damage payments from the auditor to investors in case of audit failure, but also increases litigation frictions such as attorneys' fees. The main finding is that the relationship between the strictness of the legal regime and the probability of client rejection is U-shaped. Our model suggests that in environments with moderate legal liability regimes, the client rejection rate is lower than in environments with relatively strong or relatively weak legal regimes.